PositivMasc: masculinities and violence against women among young people. Identifying discourses and developing strategies for change, a mixed-method study protocol - N Daoud; M Salazar; Claire Edwards; Margaret Scanlon; C Vives-Cases (BMJ Open)
Introduction Despite public policies and legislative changes aiming to curtail men’s violence against women (VAW) around the world, women continue to be exposed to VAW throughout their life. One in three women in Europe has reported physical or sexual abuse. Men who display unequitable masculinities are more likely to be perpetrators. VAW is increasingly appearing at younger ages. The aims of the project are fourfold: (1) to explore and position the discourses that young people (men and women, 18–24 years) in Sweden, Spain, Ireland and Israel use in their understanding of masculinities, (2) to explore how these discourses influence young people’s attitudes, behaviours and responses to VAW, (3) to explore individual and societal factors supporting and promoting anti-VAW masculinities discourses and (4) to develop actions and guidelines to support and promote anti-VAW masculinities in these settings.Methods and analysis A participatory explorative mixed-method study will be used. In Phase 1, qualitative methods will be used to identify the discourses that young people and stakeholders use to conceptualise masculinities, VAW and the actions that are needed to support and promote antiviolence masculinities. In Phase 2, concept mapping will be used to quantify the coherence, relative importance and perceived relationship between the different actions to support and promote anti-VAW masculinities. Phase 3 is a knowledge creation and translation phase, based on findings from Phases 1 and 2, where actions and guidelines to promote and support anti-VAW masculinities will be developed.Ethics and dissemination Ethical clearance has been obtained from ethics review boards in each country. Results will be disseminated through peer-reviewed publications, presentations at international conferences, policy briefs, social media and through the project online hub. With its multicountry approach, our project results seek to inform policies and interventions aimed at promoting discourses which challenge hegemonic masculinities.